Intervención fisioterapéutica en las complicaciones de pacientes con parálisis cerebral infantil espástica que acuden al Hospital General Martin Icaza, en el periodo junio – septiembre 2024. - Medina Mera, Gabriela Ernestina (2024)
Physical intervention in patients with infantile spastic cerebral palsy aims to clarify the main problems that exist in the treatment of movement disorders during the study period of this study, which will be carried out in the general hospital setting called Martín Icaza General Hospital. The study uses a descriptive, qualitative and quantitative approach to evaluate the effectiveness of the intervention, defining the independent variable (physiotherapy intervention) and the dependent variable (cerebral palsy problems). Twenty-five percent of children with cerebral palsy will be selected for the study, through surveys and interviews to collect data to ensure ethical compliance. Cerebral palsy, which affects gait and posture, is the most common cause of disability in children. Physiotherapy interventions are important and evidence-based practices should be used. This study seeks to assess how physiotherapy interventions can reduce complications such as seizures and improve patients' quality of life and motor function, highlighting the need for 'variation and standard guidelines' in the treatment of cerebral palsy in Ecuador. The importance of physiotherapy in improving patients' motor function and quality of life is highlighted. Measures such as the development of standardized policies, continuing professional education, and the promotion of social inclusion are recommended. Common complications associated with spastic infantile cerebral palsy were identified, including epilepsy and muscle contractures. These complications not only affect mobility, but also impact the quality of life of patients and their families. Early intervention and interdisciplinary collaboration are highlighted as key factors for treatment success, underlining the importance of effective communication between health professionals and parents. It is proposed to establish a continuous evaluation system to monitor the effectiveness of interventions and suggests further research to adjust and improve therapeutic approaches. The need for standardized treatment protocols and ongoing staff training is emphasized to ensure proper management of this condition.